Antenatal Care Visits and Early Detection of Pre-eclampsia among Pregnant Women - Dini Rima Fadilah; Shrimarti Rukmini Devy (Intelektual Pustaka Media Utama, 2018)
The death of pregnant women is still the world's attention in the field of health. The SDG's indicator provides one of the goals in the health field. The target to be achieved is a global maternal mortality ratio of less than 70/100,000 live births by 2030. According to WHO, preeclampsia is one of the leading causes of maternal death in the world, including Indonesia. East Java Province with the highest ranking in Indonesia. One of the cities in East Java which is the leading contributor to preeclampsia is Surabaya with 16 cases in 2016. The government carries out the treatment to reduce maternal mortality due to preeclampsia through antenatal care. This study aimed to analyze antenatal care visits for early detection of preeclampsia. The method in this research is qualitative research method with data retrieval technique using in-depth interview. Based on the results of research antenatal care visits have an effect on early detection of preeclampsia. Pregnant women who regularly make antenatal visits can prevent possible dangers of pregnancy as early as possible. So the maternal mortality rate (MMR) due to pre-eclampsia can be decreased.